2015
DOI: 10.1016/j.euroneuro.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine use in childhood and adolescent schizophrenia: A nationwide population-based study

Abstract: Early onset schizophrenia (EOS) begins in childhood or adolescence. EOS is associated with poor treatment response and may benefit from timely use of clozapine. This study aimed to identify the predictors of clozapine use in EOS and characterize the clinical profile and outcome of clozapine-treated youths with schizophrenia. We conducted a nationwide population-based study using linked data from Danish medical registries. We examined all incident cases of EOS (i.e., cases diagnosed prior to their 18th birthday… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 37 publications
4
35
1
Order By: Relevance
“…Our findings are consistent with the recent Scandinavian population study that found that 88.8% of EOS patients (mean age of onset is 16.2 years) prescribed clozapine appeared to have a favorable outcome as indicated by continued prescription redemption for 6 consecutive months (Schneider et al 2015).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are consistent with the recent Scandinavian population study that found that 88.8% of EOS patients (mean age of onset is 16.2 years) prescribed clozapine appeared to have a favorable outcome as indicated by continued prescription redemption for 6 consecutive months (Schneider et al 2015).…”
Section: Discussionsupporting
confidence: 82%
“…Periods shorter than this may reflect discontinuation caused by adverse drug reactions during titration, whereas discontinuation after 6 months is likely to be influenced by nonspecific factors affecting long-term adherence, including refusal of ongoing hematological monitoring (Schneider et al 2015). Additionally, symptomatic improvement may continue from 6 weeks to ‡6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Third, we restricted the cohort to adult individuals (≥18 years at first diagnosis of schizophrenia) since the antipsychotic treatment guidelines as well as clinical prescribing practice and response to antipsychotics differ between childhood-and adultonset schizophrenia. 31,32 Finally, all analyses were repeated with polygenic risk scores calculated based on SNPs selected using thresholds of p<0.01 and p<0.1, including 10,622 and 35,792 SNPs, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating risk factors for TR have utilised clozapine prescription rates as a proxy measure of TR ( (Nielsen et al, 2012b, Schneider et al, 2015, Stroup et al, 2014, however, given the underutilisation of clozapine in clinical practice, such studies do not measure all people with TR. Although, a few potential risk factors for treatment resistance (TR), such as poor premorbid functioning, living in less urban areas, comorbid personality disorder, longer duration of untreated psychosis (DUP), greater severity of negative symptoms, and a younger age of illness onset have been suggested (Frank et al, 2015, Martin and Mowry, 2016, Meltzer, 1997, Ortiz et al, 2013, Schennach et al, 2012, Vanelle et al, 1994, Wimberley et al, 2016, the predictive value of specific clinical and demographic factors on treatment resistance in first episode schizophrenia has not yet been widely investigated (Lin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%